Efficient cleavage of single and clustered AP site lesions within mono-nucleosome templates by CHO-K1 nuclear extract contrasts with retardation of incision by purified APE1 - Eccles, Laura J. (DNA Repair (Amst), 2015)
Clustered DNA damage is a unique characteristic of radiation-induced DNA damage and the formation of these sites poses a serious challenge to the cell’s repair machinery. Within a cell DNA is compacted, with nucleosomes being the first order of higher level structure. However, few data are reported on the efficiency of clustered-lesion processing within nucleosomal DNA templates. Here, we show retardation of cleavage of a single AP site by purified APE1 when contained in nucleosomal DNA, compared to cleavage of an AP site in non-nucleosomal DNA. This retardation seen in nucleosomal DNA was alleviated by incubation with CHO-K1 nuclear extract. When clustered DNA damage sites containing bistranded AP sites were present in nucleosomal DNA, efficient cleavage of the AP sites was observed after treatment with nuclear extract. The resultant DSB formation led to DNA dissociating from the histone core and nucleosomal dispersion. Clustered damaged sites containing bistranded AP site/8-oxoG residues showed no retardation of cleavage of the AP site but retardation of 8-oxoG excision, compared to isolated lesions, thus DSB formation was not seen. An increased understanding of processing of clustered DNA damage in a nucleosomal environment may lead to new strategies to enhance the cytotoxic effects of radiotherapeutics.